Safety, Tolerability, and Pharmacokinetics of a Novel Mitochondrial Modulator, TRC150094, in Overweight and Obese Subjects: A Randomized Phase-I Clinical Trial - Joshi, Deepa; Jamadarkhana, Prashant; Kumbhare, Suchit; Singh, Amarinder; Kotecha, Jignesh; Bunger, Deepak; Shiwalkar, Ajay; Mohanan, Anookh; Dutt, Chaitanya (Frontiers in Pharmacology, 2021)
TRC150094, a novel mitochondrial modulator, restores metabolic flexibility by improving insulin resistance in preclinical studies. The objective of this study was primarily to evaluate the safety, tolerability, and pharmacokinetics (PK) of oral TRC150094 after single ascending dose (SAD) and multiple ascending doses (MAD) in overweight/obese adult and elderly subjects and to study its effect on pharmacodynamic (PD) efficacy markers. Two double-blind, randomized, Phase-I studies, SAD and MAD, were conducted (n=46). PK assessments including maximum concentration (Cmax), an area under the plasma concentration (AUC), time to Cmax (Tmax), and elimination half-life (t½) were assessed at pre-specified time points, and PD assessments included apolipoprotein B (ApoB), triglycerides, hepatic fat by magnetic resonance spectroscopy (MRS) and cardiopulmonary exercise testing (CPET) parameters. TRC150094 was rapidly absorbed, and the AUC of TRC150094 increased in a dose-dependent manner, across all doses, in non-elderly and elderly cohorts. Cmax was more than the dose-proportional for all doses in all cohorts. Tmax ranged from 0.25 to 4 hours, and t½ ranged from 15-18 hours, making it suitable for once-daily dosing. Food did not interfere with the overall absorption of the drug. The metabolites of TRC150094 were glucuronide and sulfate conjugates, and 20% of the drug was excreted unchanged in the urine. TRC150094 at 50mg showed a trend towards improvement in triglycerides. A significant reduction in Apo B was observed after 50 mg dose (-2.34% vs. 13.24%, p=0.008), not, however, after 150 mg (8.78% vs. 13.24%, p=0.1221). Other parameters like hepatic fat and insulin sensitivity indices (HOMA-IR, MATSUDA-Index derived from OGTT) showed a trend towards improvement for the dose of 50 mg. In terms of safety, all the AEs reported were mild to moderate in severity, none of the AEs were considered definitely or probably related to treatment and there were no abnormal laboratory findings. In conclusion, the PK of TRC150094 were linear with no clinically significant food effect, TRC150094 and its metabolites suggest a lesser likelihood of drug-drug interactions. Overall, TRC150094 was safe and well-tolerated in all subjects.